Mulheres recontam Brasília: memórias candangas, teatro documentário e fabulação crítica (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
The research Memories of Candanga Women: between documentary Theater and critical fabulation focused on conducting theatrical experiments based on the stories of candanga women, found in the Federal District Public Archive (ArPDF) interviews collection, utilizing documentary theater and critical fabulation. These experiments aimed to expand the repertoire of memories regarding the diverse forms of female presence in the federal capital's history – presences that had been silenced or, at best, recalled primarily through the lens of suffering and struggle. Thus, the initiative sought to foster a sense of belonging among candanga women through documentary theater and critical fabulation.
Keywords: documentary theater; critical fabulation; memory; Candanga women; Brasília